STRATEGI PENGAJARAN BAHASA INGGRIS DASAR BERBASIS DIGITAL BAGI MAHASISWA PGSD UHN SUGRIWA DENPASAR DI ERA SOCIETY 5.0 - Trisna Dewi, Komang; Astu Werdistira, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The Society 5.0 era demands the integration of digital technology in various areas of life, including higher education. English proficiency for PGSD students is no longer merely a supplement, but a core competency, along with the return of English to the elementary school curriculum. Students of the Elementary School Teacher Education (PGSD) Study Program, as future educators, need to have adequate basic English language competency and the ability to utilize digital technology in the learning process. This study aims to analyze effective digital-based basic English teaching strategies for PGSD students at UHN Sugriwa Denpasar. This study used a qualitative approach with descriptive methods. The research subjects were PGSD students taking the Basic English course. Data collection techniques were carried out through learning observations, interviews, and documentation of the use of digital platforms. The results of the study indicate that digital-based learning strategies that utilize media such as Learning Management Systems, language learning applications, interactive videos, and digital quizzes can increase student engagement, enrich the learning experience, and help students understand vocabulary and language structures more contextually. In addition, the use of digital technology also improves students' learning motivation and communication skills. This study concludes that digital-based English teaching strategies are a relevant and effective approach to supporting learning in the Society 5.0 era, particularly for prospective elementary school teacher students.